Efektivitas Model Pembelajaran Flipped Classroom Berbantuan Google Classroom Terhadap Hasil Belajar Siswa Kelas X SMK Negeri 1 Biaro - Theresa Sisilia Tindige; Dokri Gumolung (Chemistry Department, Universitas Negeri Manado, 2022)
The aim of the study was to determine the effectiveness of the Flipped Classroom Learning Model Assisted by Google Classroom on the Learning Outcomes of Class X Students of SMK Negeri 1 Biaro. This research was conducted in class X Fisheries at SMK Negeri 1 Biaro in the 2022/2023 academic year. A total of 22 students of Class X Fisheries were selected as the research sample. Based on the N-Gain test and obtained results with an average value of 0.739 which is included in the high criteria and the N-Gain score of 73.9% is included in the criteria of being quite effective. Thus it can be concluded that the Flipped Classroom Learning Model Assisted by Google Classroom effectively influences the Learning Outcomes of Class X Students of SMK Negeri 1 Biaro.